Conceptual Categories and the Structure of Reality: Theoretical and Empirical Approaches - Paul M.W. Hackett (Frontiers Research Topics, 2019)
In this eBook, Conceptual Categories and the Structure of Reality, the title very well describes the book's content. Within the book's pages a selection of academics from a variety of human behaviour, human/social science and humanities disciplines write about their research all of which can be typified by their consideration of how categories are used to structure understanding of phenomena. These authors have considered how reality may be understood through notions such as categorial and structural ontologies, part-whole relatoinships (mereology), the qualitative, quantitative and philosophical use of the facet theory approach to research, mapping sentences and declarative mapping sentence, hermeneutics, concepts and constructs, similarities and differences. The resulting collection presents the foregoing conceptual and empirical approaches to knowledge development in general (chapter 1&3 Hackett); Phillips and Wislons' review of compositional syntax in bird calls (chapter 2); neurobehavioral decision systems (chapter 4 Foxall); representations of human psychological processes (chapter 5 Juan-Miguel López-Gil; Rosa Gil; Roberto García); free associations mirroring and its relation to self- and world-related concepts (chapter 6 Martin Kuška; Radek Trnka; Aleš Antonín Kuběna; Jiří Růžička); local knowledge and going beyond the data (chapter 7 Steven Phillips); categorical etiologies of speech sound disorders (chapter 8 Kelly Farquharson); similarity of visual appearance (chapter 9 Nao Nakatsuji; Hisayasu Ihara; Takeharu Seno; Hiroshi Ito); and a consideration of the seminal writing of David Oderberg's on the categorial classification of reality (chapter 10 Hackett).